Occurrence and management of thrombosis recurrence and bleeding in low-molecular-weight heparin-treated patients with cancer-associated thrombosis: a French nationwide cohort study - Isabelle Mahé; Gaelle Gusto; Nadia Quignot; Artak Khachatryan; Jose Chaves; Audrey Moniot; Lucas Andre; Sylvain Van Roy; Ruth Mokgokong; Laurent Bertoletti (Research and Practice in Thrombosis and Haemostasis)
Background: Rates of venous thromboembolism (VTE) recurrence and bleeding remain high in patients with cancer who are prescribed anticoagulants (ACs) such as low-molecular-weight heparin (LMWH) after an initial VTE event. Objectives: To identify patient characteristics associated with VTE recurrence and bleeding in patients receiving LMWH for cancer-associated VTE and to explore secondary AC management and clinical outcomes in these patients. Methods: An observational study was conducted using nationwide French data for adults with active cancer who were hospitalized with VTE in 2013-2018 and were reimbursed for LMWH ≤ 30 days after hospital discharge. The main outcomes were VTE recurrence and bleeding. For both outcomes, the proportions of patients who experienced the outcome were calculated for different patient characteristics. AC switching following VTE recurrence and bleeding was tracked using Anatomical Therapeutic Chemical codes. Results: A total of 31,771 patients received LMWH, of whom 1925 (6.1%) experienced VTE recurrence and 1804 (5.7%) bleeding. Most recurrent VTE and bleeding events occurred within 6 months after the initial VTE event. The proportion of patients with VTE recurrence and bleeding varied between cancer types. Most patients who experienced VTE recurrence or bleeding continued to receive LMWH. Eleven percent of patients with VTE recurrence experienced a further recurrent VTE event within 3 months. Conclusion: More than 10% of patients who received LMWH for cancer-associated VTE experienced VTE recurrence or bleeding. AC management options in this patient population should be prospectively assessed in clinical trials.